Career transitions and Social Mobility among Chinese Elite Athletes - Zhang, F.; Qiu, J.; Zhu, W. (Asian Journal of Sport & Exercise Science, 2013)
This work investigates the socioeconomic factors influencing career transitions and social mobility among retired Chinese elite athletes. We address the impact of the reform of Chinas elite sports system and the changes to the retirement policy on elite athletes careers. We analyzed survey data collected in 2010 about retired Chinese elite athletes who had formerly played professional sports on national or provincial teams (N=179, average age=24.7, female=55%). Descriptive statistics and binomial and multinomial logistic regressions were used in the analysis. The results show that after retirement, most athletes (65%) attended college because fewer job opportunities were provided by the government. Retirement at a higher age reduced the likelihood of attending college (RRR [relative risk ratio] =0.75, 95% CI [confidence interval] =0.60-0.93). Higher family social status was positively associated with finding a job (RRR=4.50, 95% CI=1.06-19.13) or attending college (RRR =7.44, 95% CI=1.88-29.42). Elite athletes with a college degree achieved higher intragenerational upward mobility in their post-retirement jobs (OR [odds ratio] =12.24, CI=2.40-62.35) than those without a college degree.